PENGARUH AKTIVITAS FISIK TERHADAP RATA-RATA KADAR GULA DARAH SEWAKTU PADA LANSIA DESA - Febriastuti, Abebi; Martin, Alfianto (Fakultas Kedokteran Universitas Tarumanagara, 2024)
Background: When a person reaches the age of over 60 years they are referred to as elderly. The elderly will experience a decrease in body function, or damage at the cellular and molecular levels that takes place slowly over a long time. This decline in body function can have an impact on increasing a person's blood sugar levels. Physical activity is known to have a very good role in maintaining a person's blood sugar levels to remain stable. However, in reality, many elderly people are less physically active due to physical limitations and lack of awareness of the importance of physical activity in old age. Objective: This study aims to determine the relationship between physical activity and average blood sugar levels in the elderly in Ngrundul Village, Klaten Regency, Central Java. Methods: Analytic research with cross sectional method and collected 237 total samples from the elderly. The variables studied were physical activity and average blood sugar levels in Ngrundul Village, Klaten Regency, Central Java. Data collection using consecutive sampling technique and data analyzed using Kruskal Wallis test method . Result and Discussions: This study found that the sig value obtained was 0.860, which indicated that there was no effect of physical activity on current blood sugar in the elderly in Ngrundul village, Klaten, Central Java. (p = 0,86). Conclusion: This study did not find any relationship between physical activity and the mean of current blood sugar levels.